Modern diagnostic methods in cutaneous T-cell lymphomas - Grzanka, Aleksandra; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Primary Cutaneous T-cell Lymphomas (CTCL) are differentiated group of limfoproliferative disorders originating from skin lymphocytes. Clinical presentation and histopathology findings usually are insufficient to make diagnosis. Additional methods are needed to diagnose CTCL. These include immunohistochemistry, immunocytochemistry and molecular methods. Particularly T-cell receptor gene rearrangement analysis may be used for diagnosing early stages of the disease, as well as for defining primary tumor site and monitoring its expansion. This article outlines the modern methods used in cutaneous lymphomas diagnostic process.